WEB SERVICE OF WORKS PLANNING USING NETWORK GRAPH - Grod , Inna; Balyk , Nadiia; Vasylenko, Yaroslav; Martyniuk, Serhii; Oleksiuk, Vasyl; Barna, Olha (Physical and Mathematical Education, 2022)
Formulation the problem. Large-scale projects of the modern society include a large number of different types of work. The network graph is the main document for planning and managing such projects. This is an information-dynamic model of the sequence of works and the relationships between them. From a mathematical point of view, the network model is a finite-oriented graph. The construction of such a schedule begins with the division of the project into clearly defined works, for which the duration is specified. It is the mathematical approach that can and should replace the still widespread mechanical approach to work planning with a scientifically sound division of the production program between departments. Most authors reveal the essence of mathematical modeling through a system of complex mathematical formulas or emphasize the use of information systems and technologies. The conducted research allowed us to draw a conclusion that some discrete process management issues (namely time management) need further consideration and research. Materials and Methods. During the study, a set of theoretical, empirical, and modeling methods were applied, in particular: systematic analysis of scientific and methodological sources, the results of domestic and foreign experience on the problem, review of existing software to determine the problem solution state and select development tools of web service, analysis of methods and technologies network graphs construction, generalization of information on the problem. Results. A review of previous research in this area has been conducted. The results of the pedagogical experiment and theoretical and methodological bases of construction of network graphs in works planning tasks are analyzed. The necessity of using the apparatus of graph theory to solve the problems of optimal work planning is substantiated. Based on the methodological strategy, a web application was developed that allows you to plan the progress of work in complex projects by building an appropriate network schedule. A brief description of the functionality and user interface of the proposed web application is provided. Conclusions. A feature of the created application is the solution to the problem of planning the implementation of complex works, involving network models, which simplifies the understanding of the model as a whole and provides optimization of the developed graph-based on mathematical methods. The program displays the results of planning in graphical and textual representation, this facilitates and makes the choice of solution obvious, allows you to monitor the progress of events, and makes adjustments to the model to improve optimization. The study was conducted within the Norwegian-Ukrainian Project CPEA-ST-2019/10067 Development of students’ mathematical competencies through Digital Mathematical Modelling (DeDiMaMo) in partnership between the Ternopil Volodymyr Hnatiuk National Pedagogical University and the University of Agder (Norway), Borys Grinchenko Kyiv University.